Gambaran Karakteristik Keluarga dan Rumah Tangga pada Balita Stunting di Kelurahan Gayam dan Kelurahan Joho Kabupaten Sukoharjo - Monicha Yudha Unsa, Nurima (Jurnal Riset Kesehatan Masyarakat, 2025)
Stunting is a form of malnutrition caused by inadequate nutritional needs and repeated infections during the first 1000 days of life. Stunting is still a national priority problem that needs to be solved in Indonesia. Family and household factors are one of the factors that cause stunting in toddlers. Gayam Village and Joho Village still have high cases of stunting in the work area of the Sukoharjo Health Center. The purpose of this study is to describe family and household factors in stunted toddlers in Gayam Village and Joho Village. The research method is in the form of descriptive observational with a cross sectional approach. The population of this study is mothers with stunted toddlers with a sample of 76 respondents. This study uses univariate analysis. The results of the study show that the majority of mothers have stunted toddlers with a history of birth weight ≥ 2500 grams. Most pregnant women are in the age range of 20-35 years with a height of ≥ 150cm and are high school/college graduates. More mothers are not working and have family income under UMR. Parity in mothers of toddlers is mostly ≤ 2. Most stunted toddlers are exposed to cigarette smoke. Parenting regarding breastfeeding is more often done inappropriately, the practice of feeding, health care, and psychosocial stimuli is mostly in the good category. It can be concluded that most of the family and household factors in stunted toddlers are in the good category.